KOTA PROBOLINGGO: DARI PANOPTIKON KE FRAGMENTED POWER - Anas Hidayat; Y.A. Widriyakara (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2018)
Title: The City of Probolinggo: From Panopticon to Fragmented Power The City of Probolinggo, was designed during the Dutch colonial administration. It is very clearly shows the pattern of the city as a city-scale panopticon, as it is mentioned in the theory of Jeremy Bentham. The city layout could be explained as follow: the resident's office (regional leader) becomes the center (as well as the supervisor) of a linear and straight government environment from the south (Jalan Raya Pos) to the north (Probolinggo Lama port). The Probolinggo resident office can spatially